CURRENT STATE OF PERSONNEL TRAINING FOR LIGHT INDUSTRY ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP - Vynogradska , Golda (Professional Pedagogics, 2022)
The relevance of the article is determined by the presence of contradictions and insufficient research into the theoretical and methodological foundations of the formation of professional competence of future sewing specialists and the need to study the possibilities of effective public-private partnership in the training of personnel for the light industry of Ukraine.Purpose: to analyze the current state of training of future qualified workers of the sewing profile on the basis of public-private partnership; to analyze the factors of development of public-private partnership in professional education of the sewing industry.Methods: study and analysis of scientific sources, educational and professional programs, analytical materials of the Committee of the Verkhovna Rada of Ukraine on Science, Education and Innovation, statistical data of the Ministry of Education and Science of Ukraine, the State Committee of Statistics of Ukraine, information materials from the websites of regional departments of vocational (professional and technical) education (further: V(VET)E), analytical and statistical materials of the Ukrainian mass media regarding the scientific and pedagogical literature on the research problem.Results: the degree of scientific development of the problem is clarified; the factors of the development of public-private partnership in professional education of the sewing industry are characterized; the activity experience of 29 domestic educational and practical centers of the sewing profile is analyzed; forms of cooperation between educational institutions and employers in the industry are analyzed.Conclusions: it has been proven that one of the most effective methods of training highly qualified workers is cooperation with social partners – employers who have modern technologies; this leads to the need to justify certain organizational and pedagogical conditions that must be created in vocational (professional and technical) and professional pre-higher education institutions; the problem of insufficient cooperation between vocational education institutions and employers in the industry regarding the balancing of the volumes and directions of training of qualified workers in accordance with the needs of the labor markets, the updating of professional and educational standards, the development of joint career guidance programs, cooperation during the implementation of a dual form of education, the joint development of educational and professional programs are revealed etc; actual tasks aimed at stabilizing the system of public-private partnership with the aim of improving personnel training for light industry are presented.
Keywords: public-private partnership in the light industry of Ukraine; vocational education; educational and practical centers of the sewing profile; qualified personnel of the sewing industry